A micro-CT approach for determination of insect respiratory volume - Shaha, Rajib Krishna (Ventricular Restraint Improves Outcomes in HF Patients with CRT, 2013)
Variation in the morphology of the insect tracheal system can strongly affect respiratory physiology, with implications for everything from pest control to evolution of insect body size. However, the small size of most insects has made measuring the morphology of their tracheal systems difficult. Historical approaches including light microscopy and scanning and transmission electron microscopy (SEM, TEM) are technically difficult, labor intensive, and can introduce preparation artifacts. More recently, synchrotron X-ray microtomography (SR-μCT) has allowed for detailed analysis of tracheal morphology of diverse insects. However, linear accelerators required for SR-μCT are not readily available, making the approach unavailable for most labs. Recent advancements in microcomputed tomography (μCT) have made possible fine resolution of internal morphology of very small insects. However, μCT has never been used to quantify insect tracheal system dimensions. We measured respiratory volume of a grasshopper (Schistocerca americana) by analysis of high resolution μCT scans. Volume estimates from μCT closely matched volume estimates by water displacement as well as literature estimates for this species. The μCT approach may thus provide a widely available, cost-effective, and straightforward approach to characterizing the internal morphology of insect respiratory systems.